Detection of Antibodies Level In Kintamani Dog Blood Serum, Post Vaccination of Rabies with Direct ELISA - Cahyana, I Putu Agus Tirta; Pharmawati, Made; Narayani, Inna (Metamorfosa: Journal of Biological Sciences, 2021)
The success of rabies vaccination is characterized by the growth of seropositive (?0,5 IU) antibody titers after vaccination. One of the tests carried out to monitor antibody growth is ELISA ( Enzyme Linked Immunosorbent Assay ). This study aims to determine the effect of different vaccine doses on rabies antibody growth in kintamani dogs. The study was conducted at Perum Taman Graha, Jimbaran and Bali Besar Veteriner (BBVet) Denpasar, Bali. The design of the study used 2 variables, namely differences in vaccine doses (0.5 and 0.75 cc) and blood collection times (1, 2 and 3 months after vaccination). The results showed that vaccine dose of 0.5 cc produced higher antibody titers than vaccine dose of 0.75 cc, however it was not significantly different based on t-test. Key word : Antibody, ELISA, Rabies